A Study of Electrocardiographic Abnormalities in Patients with Acute Cerebrovascular Events - Gadde Sudhish; Swathy Moorthy; Krishnaswamy Madhavan (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Cerebrovascular accidents have long been recognised for their debilitating impact on one’s life, posing a major contributor for morbidity and mortality. An array of cardiovascular events occur with an increased frequency among patients with cerebrovascular events in spite of no previous cardiac diseases. Electrocardiographic changes are well known to occur in patients with neurological disorders. Aim: To identify the abnormal ECG patterns associated with the type of acute stroke and determine if the specific changes in ECG associated with elevated cardiac enzymes, echocardiographic abnormalities and the patient outcomes. Materials and Methods: A total of 100 patients with no previous cardiac disease or ECG abnormality, admitted with acute stroke was enrolled in the study. All the patients underwent an electrocardiographic recording within the first two hours of admission and the abnormal findings were recorded and correlated in relation to the nature of stroke whether the ischaemic or the haemorrhagic type, the echocardiographic findings, cardiac biomarkers and the patient outcomes. The data were analysed with SPSS software and categorical variables with chi-square test. A p-value of <0.05 was considered statistically significant. Results: Among the study population, 78 patients had ischaemic stroke while 22 patients had haemorrhagic stroke. ECG changes were noted among 97 patients. The common ECG changes among both the ischaemic and haemorrhagic groups were T wave inversion and ST depression. Thirty-three patients with ECG abnormalities also had echocardiographic abnormalities in ischaemic group while seven patients had ECG and echocardiographic abnormalities in the haemorrhagic group. Thirty-two patients with changes in the ECG had elevated cardiac biomarkers. ST depression was strongly associated with elevated troponin T, CPK- MB, BNP and abnormal echocardiographic findings with a p-value of ≤0.001. Both ST segment depression on ECG and elevated CPK MB were strong predictors of mortality among patients with acute cerebrovascular events individually, with a p-value <0.001. Conclusion: ECG abnormalities were commonly seen among patients with acute cerebrovascular accidents which vary from T wave inversion to ST segment depression. CPK MB, troponin T and BNP were elevated among 32 patients with ECG changes and 40% patients with ECG changes had abnormalities noted in their echocardiogram. Mortality was slightly higher among the haemorrhagic group compared to the ischaemic stroke group, though not significant.